Trends in diagnosed anemia in the Peruvian population: A longitudinal analysis (2019–2023) - Vera Mendoza, Edwin Michel (2024)
Objective. To identify the prevalence of anemia in patients treated from January to July in the years 2019 to 2023, focusing on variables such as sex, age, and year. Methods. Blood samples were collected and analyzed from patients treated during the defned period. Anemia diagnoses were identified using ICD-10 codes. The analysis focused on variations by sex and age group. Descriptive statistics were applied using frequency tables based on the distribution of confirmed anemia cases. Results. A total of 1,048,575 confrmed anemia cases were recorded, with a significant increase from 122 cases in 2019 to 581,404 in 2023. Anemia was more prevalent in women (80.9%) than in men (19.1%). Signifcant differences in anemia prevalence were observed among age groups: 0 to 11 years (14.1%), 12 to 17 years (18.1%), 18 to 29 years (18.0%), 30 to 59 years (43.9%), and over 60 years (5.9%). Anemia frequency fluctuated throughout the year, peaking in March (14.8%) and April (15.3%). Conclusions. A continuous increase in anemia cases was observed, particularly among women. The high prevalence in certain age groups underscores the need for comprehensive prevention programs, nutritional education, and clinical monitoring.